2020
DOI: 10.12674/ptk.2020.27.1.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Proprioceptive Neuromuscular Facilitation and Static Stretching Performed at Various Intensities on Hamstring Flexibility

Abstract: Hamstring musclesHigh-intensity Low-intensity Proprioceptive neuromuscular facilitation stretching Static stretching Background: To prevent or reduce the risk of strain injury, various approaches, including stretching techniques are currently being used. The effect of proprioceptive neuromuscular facilitation (PNF) and static stretching on flexibility has been demonstrated; however, it is not clear which one is superior.Objects: This study aimed to evaluate the differences between the effects of PNF and static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Various studies have demonstrated the effects of PNF stretching on flexibility with different contraction intensities [3][4][5]. However, previous research provided torque or force values in real time, allowing subjects to identify their contrac-tion intensity values.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated the effects of PNF stretching on flexibility with different contraction intensities [3][4][5]. However, previous research provided torque or force values in real time, allowing subjects to identify their contrac-tion intensity values.…”
Section: Introductionmentioning
confidence: 99%